An analysis of the causes of compressed-gas diving fatalities in Australia from 1972-2005 - Lippmann, J.; Baddeley, Adrian; Vann, R.; Walker, D. (2013)
In order to investigate causative factors, root cause analysis (RCA) was applied to 351 Australian compressed-gas diving fatalities from 1972-2005. Each case was described by four sequential events (trigger, disabling agent, disabling injury, cause of death) that were assessed for frequency, trends, and dive and diver characteristics. The average age increased by 16 years, with women three years younger than men annually. For the entire 34-year period, the principal disabling injuries were asphyxia (49%), cerebral arterial gas embolism (CAGE; 25%), and cardiac (19%). There was evidence of a long-term decline in the rate of asphyxia and a long-term increase in CAGE and cardiac disabling injuries. Asphyxia was associated with rough water, buoyancy trouble, equipment trouble, and gas supply trouble. CAGE was associated with gas supply trouble and ascent trouble, while cardiac cases were associated with exertion, cardiovascular disease, and greater age. Exertion was more common in younger cardiac deaths than in older deaths. Asphyxia became less common with increasing age. Equipment-related problems were most common during the late 1980s and less so in 2005. Buoyancy-related deaths usually involved loss of buoyancy on the surface but decreased when buoyancy control devices were used. Countermeasures to reduce fatalities based on these observations will require validation by active surveillance.